1991
DOI: 10.3109/07853899109147933
|View full text |Cite
|
Sign up to set email alerts
|

Serum Insulin and Other Cardiovascular Risk Indicators in Children, Adolescents and Young Adults

Abstract: We wanted to determine the levels of fasting serum insulin during growth, the tracking of serum insulin, and the correlation of serum insulin with other coronary heart disease risk indicators in children and young adults. In 1986 2433 subjects, aged nine to 24 were studied, and insulin data were available from the same population in 1980 and 1983. Serum insulin levels showed a peak during puberty in both sexes and the decline in insulin continued after the age of 21. Tracking of serum insulin was only moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
48
1
4

Year Published

1993
1993
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(68 citation statements)
references
References 30 publications
15
48
1
4
Order By: Relevance
“…Adult women who had early menarche may have hyperinsulinemia, since tracking of serum insulin is observed especially in females. 35) There are only a few studies on the effect of abortion or in- Adjusted relative risk (RR) for colon cancer by age at menarche, gravida, parity, age at first birth, and the number of abortions, JACC study, 1988-1997 Person-years 1) No …”
Section: Discussionmentioning
confidence: 99%
“…Adult women who had early menarche may have hyperinsulinemia, since tracking of serum insulin is observed especially in females. 35) There are only a few studies on the effect of abortion or in- Adjusted relative risk (RR) for colon cancer by age at menarche, gravida, parity, age at first birth, and the number of abortions, JACC study, 1988-1997 Person-years 1) No …”
Section: Discussionmentioning
confidence: 99%
“…9 Obesity has been reported to correlate positively with serum insulin even in childhood, 10,11 and it has been suggested that the metabolic syndrome may already exist in children. 11 Since there appears to be a lot of clinical evidence for deleterious effects of childhood obesity on the cardiovascular system, it would be of great importance to know the actual degree of obesity-related arterial and myocardial pathology to be found in children.…”
Section: Introductionmentioning
confidence: 99%
“…9 Obesity has been reported to correlate positively with serum insulin even in childhood, 10,11 and it has been suggested that the metabolic syndrome may already exist in children. 11 Since there appears to be a lot of clinical evidence for deleterious effects of childhood obesity on the cardiovascular system, it would be of great importance to know the actual degree of obesity-related arterial and myocardial pathology to be found in children. Newman et al 1 reported that coronary or aortic fatty streaks in 35 autopsied persons with a mean age of 18 y (the majority being 15±19 y) were not related to obesity, but larger autopsy surveys on the cardiovascular system in children are few in number and have not concentrated on the effects of childhood obesity or body fat distribution patterns.…”
Section: Introductionmentioning
confidence: 99%
“…18 ± 28 This relationship has not been thoroughly examined among children, yet insulin resistance in children may be related to chronic disease later in life. 7,29,30 One complication of studying the effects of leptin on insulin is that the relationship between leptin and insulin may be bidirectional and may be modi®ed by extent of obesity and insulin resistance. 31,32 Even if elevated leptin is a consequence rather than a predictor of insulin resistance, it still may be a useful screening tool for children with early metabolic disorders.…”
Section: Introductionmentioning
confidence: 99%